Atrial thrombus detection on transoesophageal echocardiography in patients with atrial fibrillation undergoing cardioversion or catheter ablation: A pooled analysis of rates and predictors. (18th May 2021) - Noubiap, Jean Jacques; Agbaedeng, Thomas A.; Ndoadoumgue, Aude Laetitia; Nyaga, Ulrich Flore; Kengne, Andre Pascal
Abstract: Objective: To summarize data on the rates and predictors of left atrial thrombus/left atrial appendage thrombus (LAT/LAAT) detection by transoesophageal echocardiography (TEE) before electrical cardioversion (ECV) or catheter ablation (CA) for atrial fibrillation (AF). Methods: EMBASE, MEDLINE, and Web of Science Core Collection were searched to identify all studies providing relevant data and published by October 7, 2020. A random‐effects meta‐analysis method was used to pool effect size estimates. Results: A total of 85 studies were included, reporting data from 56 660 patients with AF. In patients undergoing CA and ECV, the pooled prevalence of LAT/LAAT was 1.8% and 7.5% in those not on oral anticoagulation (OAC), 1.8% and 5.5% in those taking OAC, and 1.3% and 4.9% in case of adequate OAC, respectively. According to the type of OAC, the prevalence was 2.0% and 7.6% for vitamin K antagonist, 1.3% and 3.5% for direct oral anticoagulant. Predictors of LAT/LAAT detection were nonparoxysmal AF (odds ratio [OR]: 3.6, 95% confidence interval: 2.4–5.2), hypertension (OR: 2.9, 1.2–7.0), previous stroke (OR: 3.0, 1.6–5.63), heart failure (OR: 4.3, 2.7–6.8), and CHADS2 score ≥2 (OR: 3.3, 1.9–5.8) for patients undergoing CA; and heart failure (OR: 2.8, 1.3–6.2) and the CHA2 DS2 ‐VASc score (OR: 2.55, 1.5–4.5) for those undergoing ECV. Conclusion: The prevalence of LAT/LAAT in AF patients undergoing ECV or CA varies widely, mainly due to differences in patient risk profiles and OAC types. Further research should determine whether the predictors of LAT/LAAT detection identified by this study could be used to select patients who require preprocedural TEE. Graphical abstract: Meta‐analysis of rates and predictors of left atrial thrombus in patients with atrial fibrillation. Legend: DOAC: direct oral anticoagulant; HF: heart failure; HPT: hypertension: LA: left atrial; LAA: left atrial appendage; NPAF, non‐paroxysmal atrial fibrillation; TIA: transient ischemic attack.